Retention mechanisms for ER and Golgi membrane proteins - Gao, Caiji; Robinson, David G. (Trends in plant science, 2014)
Unless there are mechanisms to selectively retain membrane proteins in the endoplasmic reticulum (ER) or in the Golgi apparatus, they automatically proceed downstream to the plasma or vacuole membranes. Two types of coat protein complex I (COPI)-interacting motifs in the cytosolic tails of membrane proteins seem to facilitate membrane retention in the early secretory pathway of plants: a dilysine (KKXX) motif (which is typical of p24 proteins) for the ER and a KXE/D motif (which occurs in the Arabidopsis endomembrane protein EMP12) for the Golgi apparatus. The KXE/D motif is highly conserved in all eukaryotic EMPs and is additionally present in hundreds of other proteins of unknown subcellular localization and function. This novel signal may represent a new general mechanism for Golgi targeting and the retention of polytopic integral membrane proteins.